Analysis Of Wristand Hand Torque Strength Among Malaysian Adults For Designing Torque Wrench: A Pilot Study - Padmanathan, Vinothini; Isa, Halim; Tan, Chen Ming (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2020)
A pilot study was conducted to measure the wrist and hand torque strength of Malaysian adults for the purpose of designing a new torque wrench for conventional milling machine. In addition, the influence of physical factors such as hand anthropometry (forearm length, forearm circumference, palm-wrist length & palm circumference), height (cm), body weight (kg) and body Mass index (BMI) in wrist and hand torque strength were also quantified in the study. This study was conducted among 38 Malaysian adults from a public university in Malaysia. The measurements of wrist and hand torque strength were carried out for dominant hand in different standing height positions (shoulder height, waist height, elbow height, and eye height) for both clockwise and anti-clockwise directions. The wrist and hand torque strength was measured by using a handheld dynamometer, Mark 10 Series R52 M3i (USA) which was attached to a vertical test rig. Furthermore, hand anthropometry, height (cm) body weight (kg), height (cm) and BMI were also measured. The study results identified that the mean wrist and hand torque strength exerted by males was 25%-60% higher than females. In addition, a significant positive correlation (p< 0.05) was found between the wrist and hand torque strength and the hand anthropometry, height (cm) body weight (kg), height (cm) and BMI. The study findings might help the respective authorities to redesign a new torque wrench that applies ergonomics principles for milling machine users in the university. Moreover, this additional information on the wrist and hand torque strength might fill the gap in the strength data for the Malaysian population, or could be utilized by ergonomics practitioners in industries